117-4x=14x+23

Simple and best practice solution for 117-4x=14x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 117-4x=14x+23 equation:


Simplifying
117 + -4x = 14x + 23

Reorder the terms:
117 + -4x = 23 + 14x

Solving
117 + -4x = 23 + 14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14x' to each side of the equation.
117 + -4x + -14x = 23 + 14x + -14x

Combine like terms: -4x + -14x = -18x
117 + -18x = 23 + 14x + -14x

Combine like terms: 14x + -14x = 0
117 + -18x = 23 + 0
117 + -18x = 23

Add '-117' to each side of the equation.
117 + -117 + -18x = 23 + -117

Combine like terms: 117 + -117 = 0
0 + -18x = 23 + -117
-18x = 23 + -117

Combine like terms: 23 + -117 = -94
-18x = -94

Divide each side by '-18'.
x = 5.222222222

Simplifying
x = 5.222222222

See similar equations:

| v^2-4v-60=0 | | -133-10x=9x+20 | | 3x+13=48-2x | | 9118+x=7x+700 | | 4(x-7)=7x-12 | | 8x^2+5-6=0 | | 135-2x=34x+19 | | 7x^2+3x-8=0 | | -75x=300 | | .75x=300 | | -75x=2100 | | (4x)2+33x+35= | | 7x=74 | | x+20=0 | | 112-6x= | | 2(d+1)+3(d+2)=23 | | 3k^2-3k-3=0 | | 3(x+2)=2(x+8) | | 4.5y-2.5=6.5 | | 2j-3(j+5)=5 | | 7(4x-20)=8x | | 2x+1.5=11.5 | | 8m+8n-7(8m-7n)= | | 7.4t+1.25=27.89 | | 5+3m=1-m | | p^2-5p+7=0 | | 0.06(10000)+.08=0.072(10000)+x | | x-5=23 | | 9x+7=7x-3 | | 12-8x=67-43x | | (X+6)(x-9)=0 | | 42y=8x-14 |

Equations solver categories